managing marketing: an applied approach - Capon,Noel (Wiley India, 2014)
Marketing is the source of insight about the market, customers, competitors and complementors and the business environment in general. Marketing is concerned with the companies long run relationships with customers as well as its short run sales activity. Thus marketing is a major organizational thrust, not just a responsibility assigned to a single functional department. For this reason, Managing Marketing - An Applied Approach emphasizes the role of marketing in creating value for customers -this leads to the creation of value for other firm stakeholders, including shareholders and employees. Managing Marketing - An Applied Approach is about understanding how to develop market strategy, implement market offers and manage the marketing process. In addition to the dynamic material integrated into the textbook via online resources, it has LIVE SIMULATIONS to engage students better, which come free. Simulations serve to enhance student engagement and enable content retention. These short and cost-effective simulations developed keeping the learning pedagogy of understanding a concept, practicing it and applying it to a LIVE case can be used in a single session. SIMULATION 1: Customer Lifetime Value SIMUALTION 2: Media Planning To access simulations, please follow the following steps: 1.Visit the link below: http://www.wileyindia.com/ManagingMarketing 2.'Register' by filling in the details in the registration form, using the scratch code given at the inside back cover. 3.Click on “Access Simulation” button on the page. The Marketing Toolkit No matter how well written a textbook, the only way to really learn marketing is by doing it. You simply have to take the ideas, concepts and frameworks and put them into practice. The Marketing Toolkit is a companion volume to Managing Marketing - An Applied Approach. Each chapter contains a set of tried and true experiential exercises designed to help the user prepare a strategic marketing plan - analyze a marketing situation, develop a market strategy and design a series of implementation programs. Other Supplements For Instructors Test item file. PowerPoint files Case studies For students Electronic flash cards. Financial analysis for marketing decisions. Three other learning sources accessible via the Internet (o-codes or QR codes) ·Marketing Enrichment ·Videos ·Audios